2018
DOI: 10.1039/c8ra06503a
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptome and proteome analyses reveal molecular mechanisms for formation of replant disease in Nelumbo nucifera

Abstract: Complementary transcriptomic and proteomic analyses unveiled the mechanism of replant disease in Nelumbo nucifera, a widely planted aquatic crop in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…DEGs were enriched in plant hormone signal transduction, MAPK signaling pathway-plant, phenylalanine metabolism and plant pathogen interactions under cinnamic acid treatment. Dong C. et al (2018) found that phenylpropanoid biosynthesis, flavonoid biosynthesis, metabolic pathways and plant MAPK signaling pathways were significantly activated in the roots of Nelumbo nucifera . In this study, it was found that the DEGs of patchouli were significantly enriched in GO terms such as metabolic process, stress response, transporter activity, structural and molecular activity.…”
Section: Discussionmentioning
confidence: 97%
“…DEGs were enriched in plant hormone signal transduction, MAPK signaling pathway-plant, phenylalanine metabolism and plant pathogen interactions under cinnamic acid treatment. Dong C. et al (2018) found that phenylpropanoid biosynthesis, flavonoid biosynthesis, metabolic pathways and plant MAPK signaling pathways were significantly activated in the roots of Nelumbo nucifera . In this study, it was found that the DEGs of patchouli were significantly enriched in GO terms such as metabolic process, stress response, transporter activity, structural and molecular activity.…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon led directly to a decline in the ability of patchouli roots to absorb nutrients and water under continuous cropping, thereby reducing crop yield and quality. Furthermore, studies have revealed that continuous cropping aggravates the degree of cell membrane lipid peroxidation, enhances or inhibits the activities of the plant protective enzymes POD, SOD, and CAT, increases the level of MDA, and damages the normal structure and function of the membrane (Zhang et al, 2010(Zhang et al, , 2011Dong et al, 2018). In this study, we examined the influence of continuous cropping on some physiological and biochemical characteristics of patchouli.…”
Section: Continuous Cropping Significantly Changes the Physiological ...mentioning
confidence: 97%
“…The F. commune in the soil initially invades the roots asymptomatically, and then colonizes the vascular tissues, causing wilting, necrosis, and yellowing of the above-ground parts. Cultivating a single crop for a long period on the same plot easily leads to the accumulation of pathogens and aggravates the occurrence of Fusarium wilt ( 8 ). Rhizome rot was first reported to be caused by F. oxysporum Schl.…”
Section: Introductionmentioning
confidence: 99%